The universal non-neuronal nature of Parkinson's disease: A theory - Valente, André; Adilbayeva, Altynay; Tokay, Tursonjan; Rizvanov, Albert (PeerJ PrePrints, 2015)
Various recent developments of relevance to Parkinson's disease (PD) are discussed and integrated into a comprehensive hypothesis on the nature, origin and inter-cellular mode of propagation of late-onset sporadic PD. We propose to define sporadic PD as a characteristic pathological deviation in the global gene expression program of a cell: the PD expression-state, or PD-state for short. Although a universal cell-generic state, the PD-state deviation would be particularly damaging in a neuronal context, ultimately leading to neuron death and the ensuing observed clinical signs. We review why age accumulated damage caused by oxidative stress in mitochondria could be the trigger for a primordial cell to shift to the PD-state. We put forward hematopoietic cells could be the first to acquire the PD-state, at hematopoiesis, from the disruption in reactive oxygen species (ROS) homeostasis that arises with age in the hematopoietic stem-cell niche. We argue why, nonetheless, such a process is unlikely to explain the shift to the PD-state of all the subsequently affected cells in a patient, thus indicating the existence of a distinct mechanism of propagation of the PD-state. We highlight recent findings on the intercellular exchange of mitochondrial DNA and the ability of mitochondrial DNA to modulate the cellular global gene expression state and propose this could form the basis for the intercellular propagation of the PD-state.
Keywords: Parkinsons disease; Neurodegenerative diseases; Mitochondria